Apolipoproteins and liver parameters optimize cardiovascular disease risk-stratification in nonalcoholic fatty liver disease. Issue 12 (December 2021) - Wu, Tingfeng; Ye, Junzhao; Gong, Xiaorong; Li, Xin; Shao, Congxiang; Li, Fuxi; Lin, Yansong; Ma, Qianqian; Mai, Weiyi; Wang, Wei; Feng, Shi-Ting; Zhong, Bihui
Abstract: Background: Advanced Non-alcoholic fatty liver disease (NAFLD) is associated with increased risk of cardiovascular disease (CVD). Aim: We determine whether combinations of ultrasound graphic steatosis grades, fibrosis scores and apolipoprotein levels add value to CVD risk prediction in NAFLD patients. Methods: The retrospective cohort study enrolled 10, 453 individuals (3519 NAFLD; 6934 non NAFLD) from 2004 to 2018. Hepatic ultrasound measurements, lipid and apolipoprotein profiles, Fibrosis-4 and the NAFLD fibrosis scores (NFS) were assessed. The primary outcome included both clinical and subclinical CVD. Results: During 116-month follow-up period, there were 957 clinical and 752 subclinical CVD events. NAFLD patients had a higher incidence of CVD than non NAFLD patients as the steatosis degree, NFS, and FIB4 scores increased (25.1% vs 11.9%, Log Rank: p  < 0.001). For the lipid and apolipoprotein profiles excluding triglyceride or ApoE, subjects with varied steatosis severity in the upper two tertiles had different risk of CVD ( p for interaction < 0.001). A nomogram model combination of Framingham Risk Score (FRS), NFS and apolipoprotein profiles presented a higher AUC than FRS in a time-dependent ROC curve (0.816 vs 0.752, p  < 0.001). Conclusion: The novel risk score considering ultrasonography-defined steatosis grades, non-invasive liver fibrosis scores and apolipoprotein profiles accurately predicted the 10-year risk of CVD.